Analisis Perencanaan dan Pelaksanaan Pembangunan Infrastruktur Desa serta Dampaknya terhadap Partisipasi dan Kesejahteraan Masyarakat : Studi di Desa Pentadio Barat - Alexander Badjuka; Zavicka Aulia Natasya; Siti Nurain Tuna; Siti Fadila Atjil (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the problems of rural infrastructure development in Pentadio Barat Village, particularly focusing on planning constraints, implementation challenges, and community participation in the development process. This research employs a descriptive qualitative approach, with data collected through interviews with the Village Secretary. The findings indicate that the main constraints in infrastructure development are limited budget allocation and lengthy bureaucratic procedures, especially for projects under the authority of district and provincial governments. In addition, community participation in development planning has been conducted through village deliberation forums; however, it remains largely formal and not fully participatory. The village government also supports the local economy by facilitating access to external assistance from various agencies, although this support is still highly dependent on external sources. Overall, development implementation is considered to be in accordance with planning, although discrepancies may occur, particularly in externally funded programs. This study concludes that rural development problems are both structural and participatory in nature, requiring improvements in planning, budgeting, and active community involvement to achieve sustainable development outcomes.